STRATEGI PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SD - Rosbianti; Ainun Bazirah; Nurul Aulia Putri (STKIP Subang, 2026)
This study aims to analyze the effectiveness of the Inquiry-Based Learning (IBL) model in improving the learning outcomes of elementary school students. The research method employed is Library Research, gathering data from various scientific journals related to the research theme. The findings indicate that the IBL model is effective in enhancing elementary students' learning outcomes by fostering critical, analytical, and logical thinking skills. Furthermore, the IBL model increases student motivation and participation in the learning process. This study suggests that the IBL model be utilized as an effective alternative learning approach to improve student achievement. Additionally, this research aims to describe the effectiveness of inquiry learning strategies in enhancing the critical thinking skills of elementary school students. The research method used is a literature study, involving the collection, review, and analysis of relevant scientific journals. Inquiry learning strategies emphasize the process of searching, investigating, and discovering answers through critical and analytical thinking activities. Based on the analysis of several studies, the inquiry strategy is proven to enhance students' critical thinking skills through stages such as formulating problems, conducting experiments, analyzing data, and drawing conclusions. Inquiry-based learning encourages students to think creatively and actively, providing them with meaningful learning experiences. Consequently, the implementation of inquiry learning strategies is effective in improving both the critical thinking skills and the learning outcomes of elementary school students.